A Chinese family affected by lynch syndrome caused by MLH1 mutation - Shuqin Jia; Meng Zhang; Yu Sun; Hai Yan; Fangping Zhao; Ziyu Li; Jiafu Ji (BMC, 2018)
Abstract Background Lynch syndrome (LS) is caused by mutations in DNA mismatch repair (MMR) genes, which accounts for 3-5% of colorectal cancer. The risks of several types of cancer are greatly increased among individuals with LS. In this study, 4 members of a Chinese family with a MLH1 pathogenic variant, resulting in colonic carcinoma, was reported. Case presentation A 52-year-old colon cancer female was brought to us with a family history of colon cancer. Genetic counseling traced 4 members in her family with colon cancer (mother and 3 siblings including the proband) as well as other cancer types. Next generation sequencing (NGS) with a multiple gene panel including MMR genes showed a germline mutation in MLH1 (c.1852_1854delAAG, p.K618del) in all 3 affected family members and confirmed the diagnosis of Lynch syndrome. In addition, this mutation was also identified in a asymptomatic offspring, who was then recommended to a prophylactic measure against cancer. A personalized health care plan was implemented for monitoring the condition and progression of the affected individuals. Conclusion Based on public database searching followed by pedigree verification, p.K618del variant in MLH1 is a pathogenic mutation, which supported the diagnosis of LS. This case highlights the importance of diagnosis and management in patients with hereditary cancer syndromes, particularly for asymptomatic family members.